A pilot clinical assessment of biphasic asymmetric pulsed field ablation catheter for pulmonary vein isolation - Chen, Bingwei; Lv, Chang; Cui, Yingjian; Lu, Chengzhi; Cai, Heng; Xue, Zhixiao; Xu, Xinyu; Su, Siying (Frontiers in Cardiovascular Medicine, 2024)
Pulsed field ablation (PFA) is a new treatment for atrial fibrillation (AF), and its selective ablation characteristics give it a significant advantage in treatment. In previous cellular and animal experiments, we have demonstrated that biphasic asymmetric pulses can be used to ablate myocardial tissue. However, small-scale clinical trials are needed to test whether this approach is safe and feasible before extensive clinical trials can be performed. Therefore, the purpose of this experiment is to determine the safety and feasibility of biphasic asymmetric pulses in patients with AF and is to lay the foundation for a larger clinical trial. Ablation was performed in 10 patients with AF using biphasic asymmetric pulses. Voltage mapping was performed before and after PFA operation to help us detect the change in the electrical voltage of the pulmonary veins (PV). 3-Dimensional mapping system showed continuous low potential in the ablation site, and pulmonary vein isolation (PVI) was achieved in all four PV of the patients. There were no recurrences, PV stenosis, or other serious adverse events during the 12 months follow-up. The results suggest that PFA using biphasic asymmetric waveforms for patients with AF is safe, durable, and effective and that a larger clinical trial could begin.